An investigation into the benefits of distributed propulsion on advanced aircraft configurations - Kirner, Rudi (Cranfield University, 2013)
Radical aircraft and propulsion system architecture changes may be required to continue historic performance improvement rates as current civil aircraft and engine technologies mature. Significant fuel-burn savings are predicted to be achieved through the Distributed Propulsion concept, where an array of propulsors is distributed along the span of an aircraft to ingest boundary layer air and increase propulsive efficiency. Studies such as those by NASA predict large performance benefits when integrating Distributed Propulsion with the Blended Wing Body aircraft configuration, as this planform geometry is particularly suited to the ingestion of boundary layer air and the fans can be redesigned to reduce the detrimental distortion effects on performance. Additionally, a conventional aircraft with Distributed Propulsion has not been assessed in public domain literature and may also provide substantial benefits. A conceptual aircraft design code has been developed to enable the modelling of conventional and novel aircraft. A distributed fan tool has been developed to model fan performance, and a mathematical derivation was created and integrated with the fan tool to enable the boundary layer ingestion modelling. A tube & wing Distributed Propulsion aircraft with boundary layer ingestion has been compared with a current technology reference aircraft and an advanced turbofan aircraft of 2035 technology. The advanced tube & wing aircraft achieved a 27.5% fuel-burn reduction relative to the baseline aircraft and the Distributed Propulsion variant showed fuel efficiency gains of 4.1% relative to the advanced turbofan variant due to a reduced specific fuel consumption, produced through a reduction in distributed fan power requirement. The Blended Wing Body with Distributed Propulsion was compared with a turbofan variant reference aircraft and a 5.3% fuel-burn reduction was shown to be achievable through reduced core engine size and weight. The Distributed Propulsion system was shown to be particularly sensitive to inlet duct losses. Further investigation into the parametric sensitivity of the system revealed that duct loss could be mitigated by altering the mass flow and the percentage thrust produced by the distributed fans. Fuel-burn could be further reduced bydecreasing component weight and drag, through decreasing the fan and electrical system size to below that necessary for optimum power or specific fuel consumption.
Keywords: distributed; propulsion; blended; wing; body; boundary; layer; ingestion; aircraft; magneto; plasma; dynamics